Komu zależy na sekularyzacji? Fakty i życzenia dotyczące przyszłości religii w krzywym zwierciadle WEIRD (Przegląd Religioznawczy – The Religious Studies Review, 2021)
The presence of religion in the modern world is confirmed by statistics, both global data on religious identifications. Religion is a permanent feature of our world and will undoubtedly remain so in the future. However, it is not without significance that the reality of religion is described and interpreted by representatives of the WEIRD elite, who overwhelmingly do not belong to the reality being described. In other words, we must recognize the fact that religion is a subject of research for people who, at best, are not interested in it. This may mean that secularization is largely a postulate or goal (often politically implemented plan) and not a conclusion resulting from an impartial observation. Therefore, it is difficult to find scholars willing to critically judge secularization, apart from the circles clearly identifying as a denomination. I would like to highlight two authors who stand out from this background: Leszek Kołakowski and Roger Scruton. I believe that Kołakowski and Scruton can point out the benefits of the presence of religion in the modern world, and at the same time, they see what the threats of secularization are. However, are such views able to successfully compete with the mainstream in the humanities and social sciences? I base my doubts about this, inter alia, on statistical data and the latest publications.